Deficit irrigation for rice farming with production risk due to weather variability. (May 2019) - Wibowo, R P; Sumono,; Rizaldi, T
Abstract: Deficit irrigation is one of the keys in overcoming the problem of weather variability and limited water resources. Farmers can reduce the amount of irrigation water use without affecting too much on the productivity of rice plants by using deficit irrigation. The level of deviation of rice production increases when the water level changes between the ranges of 0-2.5 cm. The tendency to decrease from the level of deviation of agricultural production is seen when the water level increases in the range of 2.5-10 cm. At a water level of 12.5 cm there is a considerable increase in deviation. However, there was a significant decrease in the level of deviation of rice production when the water level was at 15 cm. Based on this, it can be concluded that the risk management of rice production will be better when the water level is above 2.5 cm and below 15 cm. The results of this study not only can be used for the development of risk-based farmers' decision models but can also be used as input for the development of government policies in resource sharing and development of agricultural insurance